The Destiny of Postoperative Residual Ventricular Septal Defects After Surgical Repair in Infants and Children. Issue 4 (July 2020) - Bibevski, Steve; Ruzmetov, Mark; Mendoza, Laura; Decker, Jonathan; Vandale, Breanna; Jayakumar, Kaimal A.; Chan, Kak Chen; Bove, Edward; Scholl, Frank G.
Purpose: Residual ventricular septal defects (rVSDs) of small size are commonly seen on transesophageal echocardiography after surgical repair. This study aimed to determine the destiny of rVSD found on intraoperative echocardiogram. Methods: Patients undergoing surgical repair of VSD as the primary procedure with available intraoperative and discharge echocardiograms between 2007 and 2017 were reviewed. Presence of an rVSD on intraoperative echo triggered review of discharge echo and of subsequent follow-up echocardiograms. Results: One hundred four patients were analyzed. The mean age and weight for the entire cohort were 1.4 ± 2.9 years (median, 5.4 months; range, 29 days to 14 years) and 8.8 ± 9.9 kg (median, 5.1 kg; range, 2.7-58 kg), respectively. Sixty (57%) patients had rVSD at discharge, with mean size of residual VSD of 1.38 ± 0.92 mm (mode, 0.6; median, 2.2 mm; range, 0.5-3.9 mm). The mean follow-up time was 3.7 ± 3.1 years (range, 1 month to 9.3 years). Among those with rVSD at discharge, a residual shunt persisted in 73% at one-month follow-up. On follow-up at three years postdischarge, of the 60 patients with early rVSD, 6 had a persistent rVSD (10%) with a mean diameter of 3.0 ± 0.8 mm (range, 2.4-3.9 mm). Conclusions: Residual VSD after surgical repair is detected frequently on postoperative echocardiogram. The presence of rVSD was not associated with any preoperative, intraoperative, or postoperative factors. By three years of follow-up, only six patients continued to demonstrate rVSD with a mean diameter of 3 mm, suggesting that defects 3 mm or greater may be less likely to close spontaneously after three years.